A novel homemade simulator for training and assessing competency of totally implantable venous access port implantation via venous cutdown. Issue 2 (7th February 2022) - Chen, Chia-Lin; Jen-Huei Yeh, Vicky; Yeh, Yi-Ting
Abstract : Total implantable venous access port (TIVAP) by cephalic vein cutdown (CVCD) is one of the first procedures surgery residents can be performed independently under supervision. There is currently a lack of affordable simulators for teaching and assessing TIVAP competency to improve patient safety. A panel of 10 experts divided the TIVAP by CVCD procedure into 9 steps. A homemade, low-cost (3 USD) simulator was then designed for practicing standardized procedural steps in the context of a simulation-based mastery learning course. Residents were given a simulator for at-home practice and completed a survey evaluating the simulator and their learning experience. Twenty-eight first-year surgery residents participated in the course and completed the survey. They were highly satisfied with the simulator (mean score = 8.7 of 10) and generally agreed with its anatomical appearance and functional fidelity. They also appreciated the educational value of using this simulator to learn and practice basic techniques and procedural steps. Our novel, homemade simulator of CVCD TIVAP implantation is a cost-effective way of achieving procedural competence of a basic operation for inexperienced surgery residents. We envision the same principle can be applied to other procedures to enhance resident education.